Drug repurposing and emerging adjunctive treatments for schizophrenia - Bumb, Jan Malte; Enning, Frank; Leweke, F. Markus (Expert opinion on pharmacotherapy, 2015)
Introduction: Schizophrenia is a frequent disorder, which substantially impairs patients’ quality of life. Moreover, the burden of illness for patients, their families and for the society, in general, is substantial. Nevertheless, the understanding of the pathophysiology of this syndrome, concise diagnostic methods and more effective and tolerable treatments are still lacking. Thus, innovative approaches and the exploration of new territories are required. Areas covered: An overview of repurposed drugs and emerging treatments for schizophrenia is presented, focusing on randomized, controlled trials and meta-analyses. Expert opinion: Despite many years of drug research, several needs in the treatment of schizophrenia including the safety and tolerability, stage-dependent and personalized approaches, as well as drug delivery and sustainability have not been addressed sufficiently. Given the current failure of a number of mechanistically new drugs, repurposed compounds may serve as alternative and/or adjunctive agents for schizophrenic patients and for treatment refractory patients in particular. Anti-inflammatory drugs (e.g., acetylsalicylic acid, celecoxib and minocycline), as well as N-acetylcysteine, a precursor of the major antioxidant glutathione, hormones (e.g., estrogen, raloxifene and oxytocin), glutamatergic (e.g., glycine and d-serine) and nicotinergic compounds, ‘nutraceuticals’ (e.g., ω-3 fatty acids) and cannabidiol, an endocannabinoidmodulator, represent promising agents in this field.
Gesehen am 29.11.2017